Tonsillar Extraintestinal Enteropathy-Associated T-Cell Lymphoma in a Patient With Celiac Disease. Issue 7 (6th July 2022) - Kronsten, Victoria T.; Gosson, Caroline; Al-Khatib, Alhamza; Bagwan, Izhar; Worthington, Tim; Muthalali, Sneha; Ethell, Mark; Lim, Guan; Youd, Philippa
ABSTRACT: Enteropathy-associated T-cell lymphoma (EATL) is a rare but serious complication of celiac disease. Diagnosis is challenging. Patients can present with weight loss, abdominal pain, and diarrhea or acutely with bowel perforation or obstruction. Patients often present with advanced disease. Malnutrition further limits treatment options. Early diagnosis is important to start aggressive treatment strategies. However, even with prompt diagnosis, prognosis remains poor with a high mortality rate. We report the first documented case of sole tonsillar involvement, a rare extraintestinal and extranodal site of disease, leading to EATL diagnosis. We also highlight some of the challenges in diagnosing EATL.